Cohort profile: The PreEclampsia, Angiogenesis, Cardiac dysfunction and Hypertension (PEACH) Study. Issue 6 (11th August 2022) - Persson, Lisa Kristine Grange; Lihme, Frederikke Fog; Basit, Saima; Larsen, Maria Oku; Scheller, Nikolai Madrid; Andersen, Anita Sylvest; Halse, Karen Green; Thorsen‐Meyer, Annette; Sørensen, Karina Meden; Wohlfahrt, Jan; Melbye, Mads; Pihl, Kasper Kai Østrup; et al.
Abstract: Background: Hypertensive disorders of pregnancy (HDP) remain a leading cause of maternal morbidity and mortality worldwide, with implications for maternal and neonatal well‐being in the short term and for long‐term maternal cardiovascular health. Although the mechanisms behind HDP remain incompletely understood, evidence suggests that preeclampsia in particular is a syndrome with more than one distinct subtype. Objectives: The PEACH (PreEclampsia, Angiogenesis, Cardiac dysfunction, Hypertension) Study was established to identify new HDP subtyping systems reflecting aetiology and prognosis and to find markers of later cardiovascular disease risk associated with preeclampsia. Population: The PEACH Study recruited pregnant women referred to two Copenhagen‐area hospitals with suspected preeclampsia (mean gestational age at enrolment: 36.7 weeks) and a group of frequency‐matched pregnant women planning delivery at the same hospitals and healthy when enrolled mid‐pregnancy. Design: Prospective, longitudinal pregnancy cohort. Methods: Participants underwent repeated third‐trimester blood sample collection, longitudinal cardiac function assessments using the USCOM‐1A during the third trimester and at 1 year postpartum and collection of placental samples immediately after delivery. Medical information was abstracted from medical records and hospital databases. Preliminary results: During 2016–2018, we recruited 1149 pregnant women, of whom 1101 were followed to delivery. Among 691 women enrolled with suspected preeclampsia, 310 and 172 developed preeclampsia and gestational hypertension respectively. Among 410 women with healthy pregnancies when enrolled mid‐pregnancy, 37 later developed hypertensive disorders of pregnancy. Of 1089 women still in the cohort 1 year postpartum, 578 (53.1%) participated in the follow‐up assessment. Conclusions: The PEACH Study's rich data from women with and without HDP will enable us to identify new, clinically useful HDP subtypes to aid in decision‐making regarding monitoring and treatment. Continued postpartum follow‐up will help us develop algorithms to identify women at risk of persistent postpartum cardiac dysfunction and later cardiovascular disease after pregnancies complicated by HDP.